Quantification of Some Phenolic Acids in The Leaves of Melissa officinalis L. from Turkey and Bosnia - Ibragić, Saida; Salihović, Mirsada; Tahirović, Ismet; Toromanović, Jasmin (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2014)
Melissa officinalis L. (lemon balm) contains many potentially biologically active compounds, including the caffeic acid (CA), chlorogenic acid (CGA), rosmarinic acid (RA), succinic acid, ursolic acid and thymol. In this study, using the HPLC-ED system, determinations of gallic acid (GA), CGA, RA and CA were performed in hot water extracts of lemon balm. Analyses of GA, CGA, CA and RA were performed in supernatants of lemon balm leaf extracts. The standard solutions of GA, CGA, CA and RA were prepared by dissolving pure substances in the mobile phase. The lemon balm leaves (fresh weight) from Bosnia contained 0.38 mg/g GA, 0.25 mg/g CGA, 0.14 mg/g CA and 5.10 mg/g RA. The lemon balm leaves from Turkey had a higher CA content (0.71 mg/g), while the GA, CGA and RA content was lower (0.22 mg/g, 0.23 mg/g and 0.24 mg/g, respectively). Having many beneficial properties due to the phenolic compounds, lemon should be used as a supplement to a balanced diet.